Application of Contingent Valuation Method on Economic Valuation of Coral Reef Ecosystems in Gili Gede Marine Area, West Nusa Tenggara - Muhammad Amri Akbar; Mansur Afifi; Diswandi Diswandi (PT. Publikasiku Academic Solution, 2023)
The most obvious way to measure non-market value is to question individuals directly about their willingness to pay for a good or service. This study evaluates the economic value of coral reef ecosystems using the contingent valuation method (CVM) technique by measuring the willingness to pay the community. Furthermore, this study aims to analyze the factors that influence the willingness to pay (WTP) and the amount of the value of the community's willingness to pay (WTP) for the conservation of coral reef ecosystems in Gili Gede waters. Sample determination in this study used purposive sampling techniques with interview structured data collection techniques guided by questionnaires. Data analysis used logistic regression for factors affecting WTP and multiple linear regression for factors affecting WTP values. The results of this study found that the average WTP value of the community was Rp. 7,257 / person in the mandatory scenario and Rp. 4,685 / person in the voluntary scenario. Factors that affect the willingness to pay the community for coral reef conservation fees in the Gili Gede fishing area are education and concern for the environment. For factors that affect the amount of the value of willingness to pay the community for coral reef conservation fees in the Gili Gede fishing area in the mandatory scenario are education, domicile and concern for the environment and in the voluntary scenario are gender, education, domicile and concern for the environment